Comparisons of MN2S2vs. bipyridine as redox-active ligands to manganese and rhenium in (L–L)M′(CO)3Cl complexes. Issue 16 (21st March 2017) - Lunsford, Allen M.; Goldstein, Kristina F.; Cohan, Matthew A.; Denny, Jason A.; Bhuvanesh, Nattamai; Ding, Shengda; Hall, Michael B.; Darensbourg, Marcetta Y.
Abstract : Electronic communication was established for a heterobimetallic complex which upon reduction at one metal center modulates ligand loss and subsequent electron uptake at the second metal. Abstract : The bipyridine ligand is renowned as a photo- and redox-active ligand in catalysis; the latter has been particularly explored in the complex Re(bipy)(CO)3 Cl for CO2 reduction. We ask whether a bidentate, redox-active MN2 S2 metallodithiolate ligand in heterobimetallic complexes of Mn and Re might similarly serve as a receptor and conduit of electrons. In order to assess the electrochemical features of such designed bimetallics, a series of complexes featuring redox active MN2 S2 metallodithiolates, with M = Ni 2+, Fe(NO) 2+, and Co(NO) 2+, bound to M′(CO)3 X, where M′ = Mn and Re, were synthesized and characterized using IR and EPR spectroscopies, X-ray diffraction, cyclic voltammetry, and density functional theory (DFT) computations. Butterfly type structures resulted from binding of the convergent lone pairs of the cis -sulfur atoms to the M′(CO)3 X unit. Bond distances and angles are similar across the M′ metal series regardless of the ligand attached. Electrochemical characterizations of [MN2 S2 ·Re(CO)3 Cl] showed the redox potential of the Re is significantly altered by the identity of the metal in the N2 S2 pocket. DFT calculations proved useful to identify the roles played by the MN2 S2 ligands, upon reduction of the bimetallics, in altering the lability of the Re–Cl bond and the ensuing effect on the reduction of Re I to Re 0 .